The impact of the Maritime Labor Convention on seafarers' working and living conditions: an analysis of port state control statistics - Marina Liselotte Fotteler; Despena Andrioti Bygvraa; Olaf Chresten Jensen (BMC, 2020)
Abstract Background The Maritime Labour Convention, 2006 (MLC2006) entered into force in August 2013 and is a milestone for better working and living conditions (WLC) for seafarers. As of March 2020, 96 countries have ratified the MLC2006, covering more than 90% of the world's shipping fleet. A system of port state control (PSC) allows ratifying countries to inspect any foreign ship arriving in their ports for compliance with the convention. It is intended as a second safety measure for the identification of substandard ships that sail all over the world. Nine regional agreements, so-called Memoranda of Understanding (MoU), have been signed to coordinate and standardize PSC inspections and to increase efficiency by sharing inspections and information. This paper uses public PSC statistics to evaluate the impact of the MLC2006. Methods A preliminary analysis using registered tonnage and MLC2006 ratification was conducted and seven MoU were selected for the analysis. The annual reports of these MoU have been viewed in September 2019. Numbers on annual inspections, deficiencies and detentions and in particular data for deficiencies related to living and working conditions and certificates and documents, have been extracted and analyzed for the years 2010 to 2017. Results Across the eight-year period analyzed, inspection numbers remained stable among all MoU authorities. Deficiencies overall and deficiencies related to WLC declined, indicating an improvement in conditions overall and an increased focus on seafarers' conditions on board. After the MLC2006 entered into force, three MoU reported WLC-ratios above 14%, while the numbers didn't rise above 10% in the other four authorities. Deficiencies related to certificates and documents did not rise significantly between 2010 and 2017. Two European MoU showed the highest ratios for deficiencies in both categories analyzed. Conclusion The analysis confirmed that an increasing attention is being paid to the inspection of working and living conditions, especially in European countries. However, a clear positive impact of the MLC2006 could not be determined from the PSC statistics in this analysis. A large variation still exists among the MoU, a fact that demands increased efforts for harmonization of PSC procedures.